Endurance neuromuscular electrical stimulation training improves skeletal muscle oxidative capacity in individuals with motor‐complete spinal cord injury. Issue 5 (11th January 2017) - Erickson, Melissa L.; Ryan, Terence E.; Backus, Deborah; McCully, Kevin K.
ABSTRACT: Introduction : Spinal cord injury (SCI) results in skeletal muscle atrophy, increases in intramuscular fat, and reductions in skeletal muscle oxidative capacity. Endurance training elicited with neuromuscular electrical stimulation (NMES) may reverse these changes and lead to improvement in muscle metabolic health. Methods : Fourteen participants with complete SCI performed 16 weeks of home‐based endurance NMES training of knee extensor muscles. Skeletal muscle oxidative capacity, muscle composition, and blood metabolic and lipid profiles were assessed pre‐ and post‐training. Results : There was an increase in number of contractions performed throughout the duration of training. The average improvement in skeletal muscle oxidative capacity was 119%, ranging from –14% to 387% ( P = 0.019). There were no changes in muscle composition or blood metabolic and lipid profiles. Conclusion : Endurance training improved skeletal muscle oxidative capacity, but endurance NMES of knee extensor muscles did not change blood metabolic and lipid profiles. Muscle Nerve 55: 669–675, 2017